Surgical intervention for left main compression syndrome due to severe secondary pulmonary hypertension - Laichun Song; Ming Xu; Chao Tao; Lei Shi; Bo Wang; Huadong Yu; Xufa Chen; Liang Tao; Xi Su (Cardiology Plus, 2017)
A 51-year-old man presented with non-ST-elevation myocardial infarction due to extrinsic compression of the left main coronary artery (LMCA) caused by a dilated pulmonary artery (PA) with secondary pulmonary hypertension and was successfully treated with surgical intervention including pulmonary angioplasty, atrial septal defect correction, and thromboendarterectomy. Imaging modalities were extremely useful in making the diagnosis and providing follow-up of LMCA compression syndrome in this case. During the follow-up, a sufficient hemodynamic improvement was obtained, without exacerbation of the PA dilatation, resulting in the absence of compression of the LMCA.